The Efforts to Improve Teacher Discipline Through Reward and Punishment System in Order to Support The Effectiveness of Teaching Learning Process in SDN 2 Jrengik in 2019/2020 Academic Year - Anggraeni . (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Cycle I showed quite significant results both in the discipline of arrival time and discipline in making learning instruments. However, it has not reached the expected target of at least 85%. Obstacles that were found for teachers who lacked time discipline were apparently caused by several things including geographical location and business at home, for example there were those who had to deliver their children first and cooking (female teachers). Reward for teachers who have been disciplined in time, disciplined in making learning instruments, and achieving curriculum targets. The rewards are in the form of praise and serve as an example for other teachers in the hope that others can follow their footsteps so that at least 85% of teachers are expected to be able to discipline both in time and in carrying out learning process activities and achieve the expected curriculum targets. Cycle II showed quite significant results both in the discipline of arrival time, discipline in making learning instrument, and overall had achieved the expected target of at least 85%. Obstacles that were found for teachers who lacked time discipline were apparently caused by several things including geographical location, and busyness at home, for example there were those who had to deliver their children first, and cooking (female teachers). Therefore, by giving rewards and punishments, it turns out that it can lead to teacher awareness of their duties and responsibilities as a professional teacher.